About the Origin of the Alphabet - Mitov, Martin (Forum Theologicum Sardicense, 2025)
Martin Mitov, About the Origin of the Alphabet. The article examines the origins of the alphabet through theories linking it to Phoenician, Hebrew, Proto-Sinaitic, and Ugaritic scripts, incorporating recent discoveries and exploring their connections with biblical archaeology.